EVALUASI MUTU REKAM MEDIS DI RS PKU 1 MUHAMMADIYAH YOGYAKARTA: STUDI KASUS PADA PASIEN SECTIO CAESARIA - Hafid Hutama; Erwin Santosa (Universitas Muhammadiyah Yogyakarta, 2016)
Background: Health carein patients who come for treatment can not be handled by one personal one. Because it isa means of communication as a source of patient information stored systematically. Medical records is one source inforrmasi well as a means of communication needed for medical services and administrative activities at the hospital. However, the management of medical records has so far hampered the low quality of medical records. Some studies reveal in completeness document medical records, doctors writing difficult to read and management that seemedsober. Likewise in PKU Muhammadiyah Hospital in Yogyakarta where management of medical records there are constraints such as incomplete filling of doctors inthe medical records. Research Methods: This research is a qualitative descriptive research with case study design. Subjects were doctors, medical record quality control manager, and supervisor of data processing in medical records. Data collected by observation, document check medical records, interview the research subjects. Research Results: Completeness of medical records at PKU Muhammadiyah Hospital in Yogyakarta It is> 75% of the completeness of the medical record documents. Data were recorded accurately, Returns medical record file on time, already the SOP charging medical records, medical records format complexity, less a maximum of organizing medical records, existing storage procedures, extermination and confidentiality in medical records, and the less the maximum guidance and supervision of the management of PKU Muhammadiyah Hospital in Yogyakarta. Conclusion: Quality of Medical Records at PKU Muhammadiyah Hospital in Yogyakarta has been good only there are some advantages that already SOP is used as a standard in filling out medical records, has maximum storage efforts, extermination and confidentiality of medical records, but there are some obstacles include limitations charging time medical record, less maximum effort organizing, and less the maximum guidance and supervision of the management.